Rapid tooling via slip casting - Seng, Mark Hung Chor. (2008)
This is an experimental research project investigating the feasibility of slip casting using silicon carbide as a method of rapid forming injection moulding tools. It presents a series of experimental studying the accuracy and repeatability achievable by the slip cast process.